2013
DOI: 10.1002/med.21285
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and Potential Applications of Mitochondria‐Targeted Antioxidants in Cardiometabolic Diseases and Type 2 Diabetes

Abstract: There is abundant evidence to suggest that mitochondrial dysfunction is a main cause of insulin resistance and related cardiometabolic comorbidities. On the other hand, insulin resistance is one of the main characteristics of type 2 diabetes, obesity, and metabolic syndrome. Lipid and glucose metabolism require mitochondria to generate energy, and when O 2 consumption is low due to inefficient nutrient oxidation, there is an increase in reactive oxygen species, which can impair different types of molecules, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 187 publications
(210 reference statements)
0
35
0
1
Order By: Relevance
“…elevation and increased ROS production trigger mPTP opening, leading to the depletion of ATP and loss of mitochondrial integrity [27,28]. Mitochondria play a key role in cardiac I/R injury by regulating energy homeostasis, and this finding is emerging as a pivotal target in cardiometabolic disease therapy [29]. Previous research has confirmed that cardiac function maintenance is critically dependent on mitochondrial oxidative phosphorylation as a major source of adenosine triphosphate (ATP), and modulating mitochondrial survival/cell-death pathways will subsequently affect cardiomyocyte apoptosis and necrosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…elevation and increased ROS production trigger mPTP opening, leading to the depletion of ATP and loss of mitochondrial integrity [27,28]. Mitochondria play a key role in cardiac I/R injury by regulating energy homeostasis, and this finding is emerging as a pivotal target in cardiometabolic disease therapy [29]. Previous research has confirmed that cardiac function maintenance is critically dependent on mitochondrial oxidative phosphorylation as a major source of adenosine triphosphate (ATP), and modulating mitochondrial survival/cell-death pathways will subsequently affect cardiomyocyte apoptosis and necrosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, an increase of ROS has previously been described in an animal model of anorexia – anx/anx mice [15] - which is in line with our observations of a decrease in O 2 consumption and ΔΨ m and an increase of ROS in human anorexic subjects. High ROS production has been related to the pathology of a high number of diseases, including atherosclerosis, cardiovascular disease, cancer and diabetes [13], [15], [17], [23][24]. However, in addition to their status as oxidative molecules, ROS also act as metabolic signalling molecules [25].…”
Section: Discussionmentioning
confidence: 99%
“…25 There are three major isoforms of uncoupling proteins, UCP-1 to -3, which belong to a family of inner mitochondrial membrane proteins that are believed to control several aspects of mitochondrial function, including ROS generation, fatty acid homeostasis, and mitochondrial biogenesis. 26 These isoforms have similarities in structure, but different tissue expressions in mammals. UCP1 is expressed primarily in brown adipose tissue, UCP2 is ubiquitous, and UCP3 is present in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%